Dinoflagellate cyst biostratigraphy of initial Neotethys transgression deposits from the Cenomanian and Turonian in the Tarim Basin, western China. (April 2022) - Zhang, Mingzhen; Du, Baoxia; Wu, Zhixiong; Dou, Longhui; Zhumahun, Abduljan; Jiaoba, Dunzhu; Jin, Peihong; Du, Zhen; Wang, Sen; Xia, Yanqing
Abstract: Under the great transgressions of the Late Cretaceous, the Neotethys Sea firstly invaded the western Tarim Basin, center Asian and this continued until the Paleogene. This study presents successive dinoflagellate cyst (dinocyst) records from the Kukebai Formaion deposited during initial transgressive periods. A total of 45 samples from the Core ZK 5-2 drilled in the southern part of the western Tarim Basin yield 78 taxa including 74 taxa of dinocysts, two genera of chlorophyte algae, and two acritarch species. Upwardly, three dinoflagellate zones are distinguished in the Kukebai Formation: Subtilisphaera perlucida (interval Zone), Cyclonephelium brevispinatum (interval zone), and Heterosphaeridium difficile (interval zone) respectively. Successive dinocyst records in this study calibrate the chronostratigraphy of the Kukebai Formation from the lower Cenomanian to the lowermost Turonian. A high abundance of Subtilisphaera perlucida and sporadic Litosphaeridium siphoniphorum can be observed in the lowest Kukebai Formation, probably indicating initial sea transgression in the Tarim Basin that took place in early Cenomanian. The distribution events of key dinocyst taxa such as the first occurrence of the H. difficile and the last occurrence of consistent occurrence of Litosphaeridium siphoniphorum, indicate that the C/T boundary interval should be approximately 183 m deep in Core ZK 5–2, at the uppermost Middle Kukebai Formation. Highlights: Successive dinoflagellate cyst records from the Tarim Basin are demonstrated. A new dinoflagellate cyst zonation scheme is proposed for the Kukebai Formation. The C-T boundary location is further calibrated. The initial Tarim transgression likely occurred at the early Cenomanian.